Surface and Catalytic Properties of the CuO/AlO System as Influenced by Doping with CeO or ZrO and by γ-Irradiation - Gamil A. El-Shobaky; Farouk M. Radwan; Abd. El-Mohsen M. Turky; Ayman Abd. El-Moemen (Adsorption Science & Technology, 2001)
The effects of doping the CuO/Al 2 O 3 system with CeO 2 or ZrO 2 , or alternatively treatment with γ-irradiation, on its surface and catalytic properties were investigated using nitrogen adsorption at −196°C, the decomposition of H 2 O 2 at 20–40°C and the oxidation of CO by O 2 at 175°C. The pure solids were prepared by wet impregnation with copper nitrate dissolved in the least amount of distilled water of finely powdered solid Al(OH) 3 precalcined at 400°C, followed by drying the resulting product and subjecting the same to calcination at 500°C. The doped solids were prepared by treating Al(OH) 3 precalcined at 400°C with a known amount of dopant, i.e. cerium or zirconyl nitrate dissolved in the least amount of distilled water, prior to impregnation with the copper nitrate solution. The amount of copper oxide thus introduced was fixed at 13.5 wt% while the amounts of dopants were varied between 1 wt% and 10 wt% CeO 2 or ZrO 2 . The results obtained indicated that ZrO 2 doping increased the degree of dispersion of the CuO phase, while CeO 2 treatment had the reverse effect. Doping the CuO/Al 2 O 3 system with CeO 2 or ZrO 2 led to an increase of 15.4% or 8.1%, respectively, in its BET surface area. The catalytic activity of the system towards the decomposition of H 2 O 2 decreased on doping with ZrO 2 but increased when CeO 2 was used as a dopant. γ-Irradiation (at 20–160 Mrad) of CuO/Al 2 O 3 solids resulted in a measurable and progressive decrease in their catalytic activity towards H 2 O 2 decomposition. In CO oxidation with O 2 , ZrO 2 treatment of the CuO/Al 2 O 3 solids brought about a progressive increase in their catalytic activity with the maximum value (a 31% increase) being observed in the presence of 3 wt% ZrO 2 but then decreasing with further increases in the amount of dopant present until the final value attained with 10 wt% ZrO 2 was smaller than that measured for the pure CuO/Al 2 O 3 catalyst sample. In contrast, the addition of the smallest amount of CeO 2 (1 wt%) led to an effective increase of 69% in the catalytic activity of the CuO/Al 2 O 3 system towards the O 2 oxidation of CO, which then decreased when further amounts of CeO 2 were added to the system although still exhibiting a catalytic activity greater than that of the undoped catalyst sample. Doping or γ-irradiation of the CuO/Al 2 O 3 system had no influence on the activation energy for the decomposition of H 2 O 2 in the presence of the resulting solid catalysts although the concentrations of catalytically active sites present on the surfaces of the solids investigated were modified by such treatment.